Volume 14: Emerging Technologies; Safety Engineering and Risk Analysis; Materials: Genetics to Structures 2015
DOI: 10.1115/imece2015-52817
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of Virtual Reality Environments for Biomedical and Engineering Applications

Abstract: Virtual Reality (VR) is one of the areas of knowledge that have taken advantage of the computer technological development and scientific visualization. It has been used in different applications such as engineering, medicine, education, entertainment, astronomy, archaeology and arts. A main issue of VR and computer assisted applications is the design and development of the virtual environment, which comprises the virtual objects. Thus, the process of designing virtual environment requires the modelling of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There have been several research works reported in the literature focusing on the development and analysis of computer-aided VR applications in medicine. However, few works have addressed the development of virtual environments for such applications [ 10 ]. A virtual environment has a great impact on the performance of the application; therefore, its importance is high.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There have been several research works reported in the literature focusing on the development and analysis of computer-aided VR applications in medicine. However, few works have addressed the development of virtual environments for such applications [ 10 ]. A virtual environment has a great impact on the performance of the application; therefore, its importance is high.…”
Section: Literature Reviewmentioning
confidence: 99%